Current Advances in the Application and Development of Lubricating Oil Additives - Danilov, A. M.; Bartko, R. V.; Antonov, S. A. (Petroleum chemistry, 2021)
This review addresses the current state of utilization of various types of lubrication oil additives and summarizes available information on the latest achievements in the development of additives. The advancement of research in this area is mainly influenced by technological progress and especially by the emergence of direct-injection engines, more stringent environmental standards, as well as the use of hydrocracked oil fractions and polyalphaolefins as the basic stock for commercial oils.